2016
DOI: 10.1093/nar/gkw1198
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative profiling of selective Sox/POU pairing on hundreds of sequences in parallel by Coop-seq

Abstract: Cooperative binding of transcription factors is known to be important in the regulation of gene expression programs conferring cellular identities. However, current methods to measure cooperativity parameters have been laborious and therefore limited to studying only a few sequence variants at a time. We developed Coop-seq (cooperativity by sequencing) that is capable of efficiently and accurately determining the cooperativity parameters for hundreds of different DNA sequences in a single experiment. We apply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 61 publications
(92 reference statements)
3
28
0
Order By: Relevance
“…As reported previously, SOX2 forms cooperative heterodimers with OCT4 on canonical DNA but is unable to cobind with OCT4 on compressed DNA (Fig. A) . In contrast, SOX17 positively cooperates with OCT4 on compressed DNA and retains the ability to heterodimerize on the canonical DNA element.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…As reported previously, SOX2 forms cooperative heterodimers with OCT4 on canonical DNA but is unable to cobind with OCT4 on compressed DNA (Fig. A) . In contrast, SOX17 positively cooperates with OCT4 on compressed DNA and retains the ability to heterodimerize on the canonical DNA element.…”
Section: Resultssupporting
confidence: 78%
“…SOX2,SOX17,OCT4 and BRN2) but are also found in other paralogous SOX and POU factors that have hitherto not been reported to dimerize in a cellular context. Yet, using quantitative dimerization assays with purified DNA‐binding domains, we have shown that many SOX‐POU combinations can form heterodimers on composite DNA‐binding sites with positive cooperativity . Hence, it is possible that the physical partnership of SOX and POU is not only restricted to SOX2, SOX17, OCT4, and BRN2 but might also occur between other SOX/POU dimer pairs in different cell types.…”
Section: Discussion and Outlookmentioning
confidence: 98%
“…We did not observe significant changes in the Sox2 binding kinetics caused by the addition of Oct4, nor vice versa ( Figures 6D-6E). Therefore, besides the position and separation of Sox2/Oct4 binding motifs, their relative direction is also important for cooperativity (Chang et al, 2017).…”
Section: Cooperativity Between Pluripotency Tfs At a Native Genomic Lmentioning
confidence: 99%
“…Clustered binding of TFs is a hallmark of cis-regulatory elements, such as promoters and enhancers, which integrate multiple TF inputs to direct gene expression. Highthroughput methods have been developed to systematically determine the binding patterns of TF pairs on DNA (Chang et al, 2017;Jolma et al, 2015;Siggers et al, 2011;Slattery et al, 2011). However, the biophysical basis for cooperative TF binding in the nucleosome context remains underexplored.…”
Section: Nonreciprocal and Conditional Tf-tf Cooperativitymentioning
confidence: 99%
“…To validate our SELEX-seq results, and to better understand the mechanism of how the mGBS specifies monomer binding, we used a modified version of specificity measured by sequencing (Spec-seq, Figure 3.3A) ) called cooperativity measured by sequencing (COOP-seq) (Chang et al 2017).…”
Section: Exploring the Mechanism Of Monomeric Binding Using Spec-seq/mentioning
confidence: 99%